(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Initial Teacher Education can better prepare student teachers by considering the competences of the teacher more broadly than their subject knowledge – provided that the competences for diversity in the classroom are well defined. Students may have roots from around the world and speak a multitude of languages but the teaching population remains largely homogenous and feels ill-prepared to teach students from such diverse backgrounds. Education systems need to make sure that teacher education opportunities equip teachers with the capacity to develop appropriate strategies for teaching and learning – especially relating to languages – as well as the ability to reflect on their own beliefs and cultural differences.